La protección penal de la seguridad e higiene en el trabajo - Garcia Cavero, Percy (Revista de Derecho, 2019)
The present article deals with the offense of non compliance with the duty of preventionof occupational risks recently incorporated in article 168-A of the Penal Code. Althoughit is a significant step in the protection of workers safety and health, the penal typecontains certain particularities that influence on the penal ascription of this offenseto employers or people in charge who break the duty of prevention. On one hand, thepenal type goes back to the labor norm on safety and hygiene at work to determinewho might be the author of the offense and when a behavior reaches penal relevance,which makes it a blank criminal law. On the other hand, the configuration of the offenseis produces with a risk on the life or health of workers, assuming the structure of anoffense of concrete danger.
Keywords: Safety and hygiene at work; blank criminal law; offense of concrete danger; labor criminal law; duty of protection